Analysis of Internal Control Policies in Detecting Fraud: A Comparative Study Between Regional Governments - Sasmita, Puteri Keshya Adisty; Panggabean, Ignasius Grendo K; Situmeang, Febyola Crisanta; Purba, Vebby Anggraeni Novita Sari; Rizkina, Miftha (Lembaga Riset Mutiara Akbar, 2025)
This study aims to analyze the effectiveness of internal control policies in detecting fraud within local governments, focusing on a comparison between the Provincial Government of North Sumatra and the Provincial Government of North Kalimantan. The research employs a descriptive qualitative approach through document analysis of two key regulations, North Sumatra Governor Regulation No. 18 of 2023 and North Kalimantan Governor Regulation No. 34 of 2023. The findings reveal that North Sumatra emphasizes a cultural approach that promotes integrity values and anti-fraud awareness, while North Kalimantan adopts a systematic technical approach through risk assessment, mitigation strategies, and indicator-based reporting systems. Each approach has its strengths, but an optimal fraud control policy would ideally integrate both cultural and technical strategies comprehensively. This underscores the importance of synergy between civil servants' integrity and measurable risk mitigation systems to achieve clean and accountable local governance.